Comparative Total Phenolic Content and Antioxidant Activity of Sida cardifolia, Abutilon indicum and Mesua ferrea - Saonere, Jyotsna Anandrao; Channawar, M.A; Deore, S.L (Free Radicals and Antioxidants)
Background: Phenolic constituents of plant are the prime source of antioxidants. Natural antioxidant biomolecules become an emerging research area of this era because of their antioxidant potential. Accumulation of free radicals results in occurrence of many degenerative diseases and produced harmful effect on body. Research evidence proved that plant phenolic constituents have an antioxidant potential and has been used for the treatment of degenerative diseases. Therefore, an attempt was taken to investigate the antioxidant activity and total phenolic content of Sida cardifolia, Abutilon indicum and Mesua ferrea. Materials and Methods: Alcoholic, hydroalcoholic and water extracts of S. cardifolia, A. indicum and M. ferrea were prepared and total phenolic content was determined by Folin Ciocalteu method, and antioxidant activity was determined by DPPH free radical scavenging method. Results: Poly phenolic Result revealed that hydroalcoholic extracts of S. cardifolia, A. indicum and M. ferrea showed maximum phenolic content than the alcoholic and water extracts. In vitro Antioxidant study revealed that hydroalcoholic extract of S. cardifolia and M. ferrea showed optimum antioxidant activity while aqueous extract of A. indicum showed maximum antioxidant activity. Conclusion: Aqueous extract of A. indicum showed maximum antioxidant activity than hydroalcoholic extract of S. cardifolia and M. ferrea.
Keywords: Polyphenolic constituents; Biomolecules; Free radicals; Oxidative stress; Degenerative diseases